PENGUATAN PARADIGMA DESENTRALISASI DALAM PENGATURAN MENGENAI PEGAWAI NEGERI SIPIL - Riris Katharina (Sekretariat Jenderal DPR RI, 2011)
Problems emerged from the implementation of decentralization of the civil servants (PNS) across the country is giving a serious threat to the central government. Some examples of problems caused by the wrongdoings of the practices of this decentralization policy are, among others, the inneutrality of the civil servants, their uncontrollable growing numbers and structure, their poor management and big gap of quality among many regions. This essay argues that decentralization paradigm is still a good choice for regulating civil servants in Indonesia but its implementing policies need improvements in many areas.